Engineering of a green‐light inducible gene expression system in Synechocystis sp. PCC6803. Issue 2 (12th December 2013) - Abe, Koichi; Miyake, Kotone; Nakamura, Mayumi; Kojima, Katsuhiro; Ferri, Stefano; Ikebukuro, Kazunori; Sode, Koji
Summary In order to construct a green‐light‐regulated gene expression system for cyanobacteria, we characterized a green‐light sensing system derived from Synechocystis sp. PCC6803, consisting of the green‐light sensing histidine kinase CcaS, the cognate response regulator CcaR, and the promoter of cpcG2 (PcpcG2). CcaS and CcaR act as a genetic controller and activate gene expression from PcpcG2 with green‐light illumination. The green‐light induction level of the native PcpcG2 was investigated using GFPuv as a reporter gene inserted in a broad‐host‐range vector. A clear induction of protein expression from native PcpcG2 under green‐light illumination was observed; however, the expression level was very low compared with Ptrc, which was reported to act as a constitutive promoter in cyanobacteria. Therefore, a Shine‐Dalgarno‐like sequence derived from the cpcB gene was inserted in the 5′ untranslated region of the cpcG2 gene, and the expression level of CcaR was increased. Thus, constructed engineered green‐light sensing system resulted in about 40‐fold higher protein expression than with the wild‐type promoter with a high ON/OFF ratio under green‐light illumination. The engineered green‐light gene expression system would be a useful genetic tool for controlling gene expression in the emergent cyanobacterial bioprocesses.